SELFCARE IN RELATION TO DIETARY COMPLIANCE FOR NUTRITION AND FLUID AMONG PATIENTS UNDERGOING HEMODIALYSIS : indonesia - Diah, Adiyati; Zulkifli (Jurnal Ilmiah Keperawatan, 2023)
The dietary intake of nutrients and fluids holds paramount importance for patients afflicted with chronic kidney disease undergoing hemodialysis, as it significantly influences their overall well-being and quality of life. Mismanaged nutritional and fluid intake may lead to adverse clinical consequences, including the development of ascites and edema. Furthermore, inadequate implementation of a well-balanced nutritional and fluid regimen can result in the depletion of muscle and fat mass, thereby impacting the daily functioning of individuals grappling with chronic kidney disease. The correlation between patients' adherence to such dietary protocols and their ability to autonomously manage self-care further underscores the significance of this study. This quantitative research was conducted using a descriptive approach and a cross-sectional design to examine patient self-care and its alignment with nutritional and fluid diet adherence among chronic kidney disease patients undergoing hemodialysis. The study was conducted at Bakti Timah Hospital and Depati Hamzah General Hospital in Pangkalpinang. This research primarily measured the degree of Self Care exhibited by Patients with Chronic Kidney Disease Undergoing Hemodialysis in adherence to a prescribed Nutritional and Fluid Diet. The findings unveiled a majority of patients (82.2%) adhering to dietary intake of essential nutrients, particularly staple foods. Conversely, the assessment of side dish consumption revealed a considerable proportion (62.7%) in the non-adherent category. Similarly, the description of mineral and water intake highlighted a majority (50.8%) falling into the non-compliant segment. Conversely, vegetable and fruit intake garnered adherence from a substantial number of patients (68.6%). Moreover, the assessment of self-care adherence in relation to vitamin consumption displayed a significant level of compliance (64.4%). In general, the self-care adherence to diet, nutrition, and fluids in hemodialysis (68.6%) was within the non-adherent category.